Unlike reactivity of mono- and binuclear imine-copper(II) complexes toward melanoma cells via a tyrosinase-dependent mechanism. (25th September 2019) - Nunes, Cléia Justino; Otake, Andréia Hanada; Bustos, Silvina Odete; Fazzi, Rodrigo Boni; Chammas, Roger; Da Costa Ferreira, Ana Maria
Abstract: The cytotoxicity of a dinuclear imine-copper (II) complex2, and its analogous mononuclear complex1, toward different melanoma cells, particularly human SKMEL-05 and SKMEL-147, was investigated. Complex2, a tyrosinase mimic, showed much higher activity in comparison to complex1, and its reactivity was verified to be remarkably activated by UVB-light, while the mononuclear compound showed a small or negligible effect. Further, a significant dependence on the melanin content in the tumor cells, both from intrinsic pigmentation or stimulated by irradiation, was observed in the case of complex2 . Similar tests with keratinocytes and melanocytes indicated a much lower sensitivity to both copper (II) complexes, even after exposition to UV light. Clonogenic assays attested that the fractions of melanoma cells survival were much lower under treatment with complex2 compared to complex1, both with or without previous irradiation of the cells. The process also involves generation of reactive oxygen species (ROS), as verified by EPR spectroscopy, and by using fluorescence indicators. Autophagic assays indicated a remarkable formation of cytoplasmic vacuoles in melanomas treated with complex2, while this effect was not observed in similar treatment with complex1 . Monitoring of specific protein LC3 corroborated the simultaneous occurrence of autophagy. A balance interplay between different modes of cell death, apoptosis and autophagy, occurs when melanomas were treated with the dinuclear complex2, in contrast to the mononuclear complex1 . These results pointed out to different mechanisms of action of such complexes, depending on its nuclearity. Graphical abstract: Cytotoxicity of dinuclear imine-copper (II) complex is mediated by reactive oxygen species, but depends further on melanogenesis and in interaction with melanin.Image 1 Highlights: Reactivity dissimilarities between dinuclear and mononuclear imine-copper(II) complexes against melanomas were monitored. Influence of UVB light and melanogenesis were particularly evaluated. Cytotoxicity is mediated by reactive oxygen species but depends further on melanogenesis and interaction with melanin. A remarkable sensitization of melanoma cells by the dinuclear complex pointed to diverse modes of action. A balance interplay of apoptosis and autophagy seems to occur.